Cu-MOF-Decorated 3D-Printed Scaffolds for Infection Control and Bone Regeneration - Ting Zhu; Qi Ni; Wenjie Wang; Dongdong Guo; Yixiao Li; Tianyu Chen; Dongyang Zhao; Xingyu Ma; Xiaojun Zhang (Journal of Functional Biomaterials)
Infection control and bone regeneration remain critical challenges in bone defect treatment. We developed a 3D-printed scaffold incorporating copper-based metal–organic framework-74 (Cu-MOF-74) within a polycaprolactone/hydroxyapatite composite. The synthesized Cu-MOF-74 exhibited a well-defined crystalline structure and rod-like morphology, as confirmed by TEM, EDS, FTIR, and XRD analyses. The scaffolds exhibited hierarchical pores (100–200 μm) and demonstrated tunable hydrophilicity, as evidenced by the water contact angles decreasing from 103.3 ± 2.02° (0% Cu-MOF-74) to 63.60 ± 1.93° (1% Cu-MOF-74). A biphasic Cu2+ release profile was observed from the scaffolds, reaching cumulative concentrations of 98.97 ± 3.10 ppm by day 28. Antimicrobial assays showed concentration-dependent efficacy, with 1% Cu-MOF-74 scaffolds achieving 90.07 ± 1.94% and 80.03 ± 2.17% inhibition against Staphylococcus aureus and Escherichia coli, respectively. Biocompatibility assessments using bone marrow-derived mesenchymal stem cells revealed enhanced cell proliferation at Cu-MOF-74 concentrations ≤ 0.2%, while concentrations ≥ 0.5% induced cytotoxicity. Osteogenic differentiation studies highlighted elevated alkaline phosphatase activity and mineralization in scaffolds with 0.05–0.2% Cu-MOF-74 scaffolds, particularly at 0.05% Cu-MOF-74 scaffolds, which exhibited the highest calcium deposition and upregulation of bone sialoprotein and osteopontin expression. These findings demonstrate the dual functional efficacy of Cu-MOF-74/PCL/HAp scaffolds in promoting both infection control and bone regeneration. These optimized Cu-MOF-74 concentrations (0.05–0.2%) effectively balance antimicrobial and osteogenic properties, presenting a promising strategy for bone defect repair in clinical applications.